2020
DOI: 10.1007/s11164-020-04268-8
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of Cu-LDH with different Cu/Al molar ratios: application as antibacterial inhibitors

Abstract: A range of Cu-LDHs has been synthesized by co-precipitation using metal nitrate precursors and sodium carbonate under varying molar ratios Cu/Al (Cu 0.05 -Al 0.15 , Cu 0.10 -Al 0.10 , Cu 0.14 -Al 0.06 , and Cu 0.15 -Al 0.05 ). The uncalcined and calcined Cu-LDHs were characterized by powder X-ray diffraction and N 2 adsorption-desorption. The uncalcined solids showed clear hydrotalcite-like crystalline phases having a particle measurement between 5 and 16 nm. The best structure is attributed to the sample Cu 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Despite the fact the aforementioned studies suggested the contribution of ROS to the antibacterial mechanism of pristine and NPs-loaded LDHs [38,47,48,53,77,78,81,133], these investigations lack real measurements of ROS and the evaluation of their role in the achieved antibacterial effect was not evident. ROS generation could be evaluated using different methods including fluorescence spectroscopy using fluorescent dye probes, ESR and chromatography methods [136].…”
Section: Limitation Of the Attribution Of The Ros Mechanism And Gener...mentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the fact the aforementioned studies suggested the contribution of ROS to the antibacterial mechanism of pristine and NPs-loaded LDHs [38,47,48,53,77,78,81,133], these investigations lack real measurements of ROS and the evaluation of their role in the achieved antibacterial effect was not evident. ROS generation could be evaluated using different methods including fluorescence spectroscopy using fluorescent dye probes, ESR and chromatography methods [136].…”
Section: Limitation Of the Attribution Of The Ros Mechanism And Gener...mentioning
confidence: 99%
“…Tabti et al synthesized a range of Cu-LDHs having different molar ratios of Cu:Al (Cu0.05-Al0.15, Cu0.10-Al0.10, Cu0.14-Al0.06, and Cu0.15-Al0.05) [48]. The antibacterial activity of the synthesized samples was estimated toward several bacterial strains, e.g.…”
Section: Antimicrobial Effect Through the Release Of Zn 2+ Cu 2+ And...mentioning
confidence: 99%
See 3 more Smart Citations